2019
DOI: 10.1186/s40104-019-0331-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of RNA editing sites in sheep

Abstract: BackgroundThe widely observed RNA-DNA differences (RDDs) have been found to be due to nucleotide alteration by RNA editing. Canonical RNA editing (i.e., A-to-I and C-to-U editing) mediated by the adenosine deaminases acting on RNA (ADAR) family and apolipoprotein B mRNA editing catalytic polypeptide-like (APOBEC) family during the transcriptional process is considered common and essential for the development of an individual. To date, an increasing number of RNA editing sites have been reported in human, roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
(50 reference statements)
2
13
0
Order By: Relevance
“…Recently, many bioinformatic tools and next-generation sequencing (NGS) techniques have been developed for detecting RNA editing events, which has enabled us to discover genome-wide RNA editing events and their molecular function. Presently, many studies for identification of RNA editing events have been performed in human ( 12 ), cattle ( 13 ), pigs ( 14 ), sheep ( 15 ), and chicken ( 16 ). Many studies have shown that dysregulation of RNA editing is associated with various human diseases, such as the presence of tumors ( 17 ), epilepsy ( 18 ), Alzheimer's disease ( 19 ), and sporadic amyotrophic lateral sclerosis (ALS) ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many bioinformatic tools and next-generation sequencing (NGS) techniques have been developed for detecting RNA editing events, which has enabled us to discover genome-wide RNA editing events and their molecular function. Presently, many studies for identification of RNA editing events have been performed in human ( 12 ), cattle ( 13 ), pigs ( 14 ), sheep ( 15 ), and chicken ( 16 ). Many studies have shown that dysregulation of RNA editing is associated with various human diseases, such as the presence of tumors ( 17 ), epilepsy ( 18 ), Alzheimer's disease ( 19 ), and sporadic amyotrophic lateral sclerosis (ALS) ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of computational methods has enabled elucidating many RNA editing sites in human and mouse [ 6 ]. More recently, a few studies have focused on the function of RNA editing in farm animals, such as cattle [ 7 , 8 ], pig [ 9 , 10 ], sheep [ 11 ], goat [ 12 ], and chicken [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data revealed novel insights into molecular pathogenesis at the global RNA level. The NEIL1 editing is also found in chickens and sheep [ 53 , 54 ]. The target duplex secondary structure and A–C mismatch at the recoding site is conserved in other vertebrate NEIL1 mRNAs, including from mouse, horse and dog, suggesting NEIL1 pre-mRNA editing also occurs in these species.…”
Section: Resultsmentioning
confidence: 99%